2017
DOI: 10.1186/s12889-017-4451-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and behaviours related to dietary salt among adults in the state of Victoria, Australia 2015

Abstract: BackgroundInformation on consumer’s knowledge, attitudes and behaviours (KABs) related to salt can be used to inform awareness and education campaigns and serve as a baseline measure to monitor changes in KABs over time. The aim of this study was to determine KABs related to salt intake among Victorian adults.MethodsCross-sectional survey conducted in Victorian adults aged 18–65 years. Participants were recruited from shopping centres located in Melbourne and Geelong and via online methods (Facebook and Consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
74
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 35 publications
14
74
2
1
Order By: Relevance
“…Even fewer reported that their food purchases were influenced by the salt level indicated (21%) [25]. In a more recent study, conducted in 2015, 89% of Australians were aware of the health risks associated with a high salt intake, 75% correctly identified salt from processed foods as being the main source of salt in the diet, but only 28% could correctly identify the maximum recommended daily intake for salt [26]. Brazilian consumers were concerned about the amount of salt (sodium chloride) in the products they consumed, regardless of educational levels, income, age, lifestyles, or health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Even fewer reported that their food purchases were influenced by the salt level indicated (21%) [25]. In a more recent study, conducted in 2015, 89% of Australians were aware of the health risks associated with a high salt intake, 75% correctly identified salt from processed foods as being the main source of salt in the diet, but only 28% could correctly identify the maximum recommended daily intake for salt [26]. Brazilian consumers were concerned about the amount of salt (sodium chloride) in the products they consumed, regardless of educational levels, income, age, lifestyles, or health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…With processed foods identified as contributing between 75–80% of total sodium intake in many industrialized countries, reformulation as a strategy to reduce population-level salt intake has resulted in part from a belief that consumers are unable to adequately monitor or change their own salt intake [ 11 ]. Indeed, recent research highlights that, while consumers are aware of high levels of salt content in processed food, they may still underestimate the extent of those salt levels [ 12 ]. By adopting a strategy of making changes to the environment as opposed to trying to change the behavior of the individual, reformulation attempts to overcome the well-acknowledged difficulty of achieving positive behavior change amongst consumers who are aware of the negative impact of salt on health, but who often fail to take action [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 In brief, participants were recruited using three strategies: (1) across four shopping centres in Victoria, (2) a Facebook advertisement campaign and (3) an online consumer research panel (Global Market Insite (GMI) Lightspeed), from September through November 2015. 23 Participants from all recruitment strategies used Qualtrics (Provo, UT; 2018), an online survey software instrument, to complete a questionnaire assessing salt-related KABs. On the questionnaire, participants were asked to indicate if they were parents or caregivers of a child or children <18 years of age.…”
Section: Methodology Study Design and Participant Recruitmentmentioning
confidence: 99%
“…23 Participants were emailed a letter containing a URL link to the plain language statement and consent form. 23 Participants were then able to access the survey via the Qualtrics link provided.…”
Section: Methodology Study Design and Participant Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation